Pendugaan Parameter Genetik Karakter Morfo-Agronomi dan Seleksi Genotipe untuk Perbaikan Genetik Jarak Pagar - Novita, Linda; Haska, Nadirman; Surahman, Memen; Wahyu, Yudiwanti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTThe recent scarcity of fuel has stimulated many efforts to remove dependence on petroleum oil by finding alternative sources of new and renewable energy. Jatropha curcas L. has been chosen as a source of biofuel that has an important role as a petroleum oil substitute, especially for producing biodiesel. Possible efforts for the development of Jatropha in Indonesia include exploration of Jatropha plants from various regions of Indonesia, introducing the plants from abroad and plant breeding. The purpose of this study was to study the genetic parameters of morpho-agronomic traits and selection of potential genotype for genetic improvement of Jatropha curcas. The experiment was conducted at the Biotech Center, BPPT from November 2011 to July 2012. The experiment was performed using a complete randomized block design with sixteen genotypes of J. curcas. Five plants were used for each genotype, with three replications. Results of this study showed that genetic diversity of the genotypes based on morpho-agronomic characters was relatively narrow, with genetic diversity coefficient ranged from 2.73% to 9.02%. The broad-sense heritability was high for all characters, ranged from 32.26% to 85.89%. None of morpho-agronomic characters observed in the 16 genotypes was directly correlated to productivity and seed oil content. Number of fruit and total seed number per bunch were the best characters for selection criteria to obtain high dry seed weight. Based on the bi-plot analysis on seed oil content and dry weight characters among the observed genotypes, LMP and CRP x PDI could be recommended as potential F1 parents to be used in constructing F2 population.Keywords: biplot analysis, broad-sense heritability, genetic diversity coefficient